Synthesis of Highly E-Selective 2-Alkenylquinolines via Lewis Acid–Catalyzed Tandem Cyclization and Olefination of Bis(trimethylsilyl)butenynylanilines with Aldehydes - Chutia, Archana; Saikia, Anil K. (Synlett, 2025)
A novel and efficient tandem strategy has been unveiled for the synthesis of 2-alkenylquinolines from bis(trimethylsilyl)butenynylanilines and aldehydes through Lewis acid–catalyzed cyclization. This innovative approach shows broad functional group tolerance, enabling access to a wide variety of 2-alkenylquinoline derivatives. Later, scalability and successful postsynthetic modification toward pharmaceutically relevant quinolines highlight the versatility and practical utility of this protocol.
Keywords: Quinolines; Aldehydes; Peterson olefination; Cyclization; Lewis acid; 2-Styrylquinoline